“Academic frictions”. Porosity of Fiction (or Theory) in Javier García Rodríguez’ Writing (Castilla. Estudios de Literatura, 2022)
The aim of this study is to deepen into the relationship between fiction and Theory from the prose work of Javier García Rodríguez, with the conviction that it is a self-conscious narrative writing in whose bosom both discourses overlap to resume a productive dialectic that enriches them. To this end, Sontag’s against interpretation premises are taken into account; we intend to find the formal function of fiction (and Theory), an erotics based on a subject —or a mask— that makes us understand that we are, unfortunately, fiction readers.
Keywords: Javier García Rodríguez; literary theory; fiction; campus literature; Susan Sontag